Preliminary clustering properties of the DESI BGS bright targets using DR9 Legacy Imaging Surveys. Issue 1 (2nd October 2021) - Zarrouk, Pauline; Ruiz-Macias, Omar; Cole, Shaun; Norberg, Peder; Baugh, Carlton; Brooks, David; Gaztañaga, Enrique; Kitanidis, Ellie; Kehoe, Robert; Landriau, Martin; Moustakas, John; Prada, Francisco; et al.
ABSTRACT: We characterize the selection cuts and clustering properties of a magnitude-limited sample of bright galaxies that is part of the Bright Galaxy Survey (BGS) of the Dark Energy Spectroscopic Instrument (DESI) using the ninth data release of the Legacy Imaging Surveys (DR9). We describe changes in the DR9 selection compared to the DR8 one and we also compare the DR9 selection in three distinct regions: BASS/MzLS in the north Galactic Cap (NGC), DECaLS in the NGC, and DECaLS in the south Galactic Cap (SGC). We investigate the systematics associated with the selection and assess its completeness by matching the BGS targets with the Galaxy and Mass Assembly (GAMA) survey. We measure the angular clustering for the overall bright sample ( r mag ≤ 19.5) and as function of apparent magnitude and colour. This enables to determine the clustering strength r 0 and slope γ by fitting a power-law model that can be used to generate accurate mock catalogues for this tracer. We use a counts-in-cells technique to explore higher order statistics and cross-correlations with external spectroscopic data sets in order to check the evolution of the clustering with redshift and the redshift distribution of the BGS targets using clustering redshifts. While this work validates the properties of the BGS bright targets, the final target selection pipeline and clustering properties of the entire DESI BGS will be fully characterized and validated with the spectroscopic data of Survey Validation.